Safety, Tolerability, and Pharmacokinetics of the β‐Site Amyloid Precursor Protein‐Cleaving Enzyme 1 Inhibitor Verubecestat (MK‐8931) in Healthy Elderly Male and Female Subjects. Issue 5 (19th June 2019) - Forman, Mark; Palcza, John; Tseng, Jack; Stone, Julie A.; Walker, Brittany; Swearingen, Dennis; Troyer, Matthew D.; Dockendorf, Marissa F.
Abstract : β‐site amyloid precursor protein‐cleaving enzyme 1 (BACE1) is required for the production of β‐amyloid peptides, which are implicated in the etiology of Alzheimer's disease. The safety and pharmacokinetics of the BACE1 inhibitor verubecestat have previously been studied in young adults aged 19–45 years. In this randomized, placebo‐controlled, phase I study (protocol MK‐8931‐006), we investigated the safety, tolerability, and pharmacokinetics of a single dose (100 mg) or multiple doses (30, 80, and 120 mg) once daily for 28 days of verubecestat in healthy elderly subjects. Safety end points were assessed at baseline and during the duration of the study period and indicated that verubecestat was generally well tolerated. Verubecestat pharmacokinetics were similar between healthy elderly male and female subjects and similar to those reported in healthy young males in previous studies. These data supported subsequent studies to assess the potential efficacy of verubecestat in subjects with Alzheimer's disease.